Heinrich Schenker: teoretik a editor - Lubomír Spurný (Musicologica Brunensia, 2012)
Heinrich Schenker divided his time between private teaching, editorial work and the series of theoretical and analytical works for which he is known today. His oeuvre is represented chiefly by three parts of the work "Neue musikalische Theorien und Phantasien" (Harmonielehre, Kontrapunkt, Der freie Satz), which form a fundamental conceptual apparatus. These parts are joined by other publications, which use Schenker's original terminology in specific analytical situations (Beethovens neunte Sinfonie, Der Tonwille, Das Meisterwerk in der Musik, etc.). The study "Heinrich Schenker: Theorist and Editor" deals with author's editorial work. This activity is with the Viennese music publisher Universal Edition associated. For Universal Edition Schenker edited selected keyboard works by C. P. E. Bach (1903) and later J. S. Bach's Chromatic Fantasy & Fugue (1910). These editions marked the beginning of a life-long involvement with composers' autograph manuscripts, copies, and early printed sources, the contents of which he sought to transmit without editorial intervention, save for footnoted commentary. Schenker's next major undertaking concerned the last five Beethoven piano sonatas, Opp. 101, 106, 109, 110, and 111, for each of which he planned a single volume containing a Foreword, the complete score, the introduction (analysis, textual commentary, and performance), and secondary literature. His work on the last five sonatas then led to his producing UE's new edition of the complete Beethoven sonatas between 1921 and 1923, each edited according to the early sources.